Non-invasive real-time genomic monitoring of the critically endangered kākāpō - Lara Urban; Allison K Miller; Daryl Eason; Deidre Vercoe; Megan Shaffer; Shaun P Wilkinson; Gert-Jan Jeunen; Neil J Gemmell; Andrew Digby (eLife, 2023)
We used non-invasive real-time genomic approaches to monitor one of the last surviving populations of the critically endangered kākāpō (Strigops habroptilus). We first established an environmental DNA metabarcoding protocol to identify the distribution of kākāpō and other vertebrate species in a highly localized manner using soil samples. Harnessing real-time nanopore sequencing and the high-quality kākāpō reference genome, we then extracted species-specific DNA from soil. We combined long read-based haplotype phasing with known individual genomic variation in the kākāpō population to identify the presence of individuals, and confirmed these genomically informed predictions through detailed metadata on kākāpō distributions. This study shows that individual identification is feasible through nanopore sequencing of environmental DNA, with important implications for future efforts in the application of genomics to the conservation of rare species, potentially expanding the application of real-time environmental DNA research from monitoring species distribution to inferring fitness parameters such as genomic diversity and inbreeding.